Immunoglobulins Levels and Complements in Patients with Brain Tumour (Meningioma and Glioma) - turki, salwa (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): The present study aims at studying the relationship between immunoglobulin IgG, IgA,IgM , as well as to C-3 and C-4 in brain tumours patients immunity (meningioms and gliomas).Methodology: Forty sera of brain tumour patients were included 20 glioma and 20 meningioma wastested to determine the levels of IgM, IgG IgA, C-3 and C-4 by using single radial immune-diffusiontechnique and compared with 20 apparently healthy blood donors.Results: The study revealed a significant decreasing in IgG levels in glioma as compare to meningiomaand control. The concentration of two other serum immunoglobulins and complement in bothmeningioma and glioma show no significant differences with those in control group.Recommendations: The study recommends using serum and tissues in molecular level in other type ofbrain tumour with different grades.